4-2(х+3)=4(х-5)
Зачем тож самое написала
4-2х-6=4х-20
4-2х-6-4х+20=0
-6х+18=0
6х=18/6
х=3
4-2х-6=4х-20
4-2х-6-4х+20=0
-6х+18=0
6х=18/6
х=3

Ответы и объяснения

  • Donimic
  • почетный грамотей
2013-10-03T19:48:50+04:00
4-2(x+3)=4(x-5)
4-2х-6=4х-20
-2х-4х=6-4-20
-6х=-18
х=(-18)/(-6)
х=3
Проверка:
4-2(3+3)=4(3-5)
4-2*6=4*(-2)
4-12=-8
    -8=-8
Ответ: 3
4-2(x+3)=4(x-5)
4-2х-6=4х-20
-2х-4х=6-4-20
-6х=-18
х=(-18)/(-6)
х=3
Проверка:
4-2(3+3)=4(3-5)
4-2*6=4*(-2)
4-12=-8
-8=-8
Ответ:--- 3
2013-10-03T19:50:25+04:00